(3eSFhdjI GdHfc Yf GdhaGA HGdTjc GdeRhQ (B/s - (3MeGO eUWai YRHs; (3GdSjO eMeO eMeO GdjeGfjs; (3LGeYI CSjhWs (3cdjI GdMbhbs ((3CSjhW(B:s (3cdjI GdMbhb (B- (3LGeYI CSjhW,s, 1991)
(3JMOK GdHGMK ai QSGdJg Yf bjGe GdJRGe GdHfc HOaY bjeI GdTjc hbSe GdJRGe GdHfc Gdi KdGKg GbSGe aai GdbSe GdGhd JMOK Yf eSFhdjI GdHfc YfO GdhaGA HGdTjc , hajg KdGKg YfGUQ aGdGhd bQjfI UMI GdhaGA hGdKGfi fWGb eSFhdjI GdHfc Yf GdhaGA HGdTjc GdeRhQ GeG GdKGdK GdeTcdI ai GdbGfhf GdebGQf hJcde ai GdbSe GdKGfi Yf GdGSGS GdbGfhfi deSFhdjI GdHfc , hajI YfUQGf GdGhd NWC GdHfc GSGS GdeSFhdjI hGdKGJi GdNWQ Gdegfi GSGS GdeSFhdjI hTQM ai GdbSe GdKGdK hSGFd GdMeGjI VO JRhjQ GdTjc , hajg YfUQGf GdGhd GdMeGjI GdeUQajI hGdKGfi GdMeGjI GdLfGFjI (B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI CSjhW, cdjI GdMbhb, bSe GdbGfhf GdJLGQj (B1996.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 672-728 (3UaMIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdJRGe GdHfc HOaY GdTjcs; (3eSFhdjI GdHfc hGdhaGA HGdTjcs; (3bQjfI UMI GdhaGAs; (3NWC GdHfc GdJbUjQjs; (3GdMeGjI GdeUQajIs; (3GdTjc GdeSWQs; (3GdMeGjI GdLfGFjIs; (3GdYbGH Ydi GdTjc GdeRhQs; (3QSGFd LGeYjIs -- (3LGeYI CSjhWs